Training Analysis in Improving Performance of Parking Workers in Pamulang Tangerang South Shop Houses - Maswarni Maswarni; Nofiar Nofiar (Jurnal Ad'ministrare, 2020)
The parking attendant, the person who helps arrange the vehicles in and out of the parking lot. The purpose of this study was to analyze training in improving the performance of parking workers in Ruko Pamulang, South Tangerang. This study uses qualitative research with the Focus Group Discussion method. Sources of data in this study, namely documents, archival records, interviews, direct observation, participant observation, and physical devices. The population in this study consisted of 12 people. In analyzing the various data coming in, researchers used the Chain of Evidence. Based on the results of the study it can be concluded that the performance of the parking attendant is quite good. Aspects of work quality have not been fulfilled to the full.